1972
DOI: 10.1007/bf00368965
|View full text |Cite
|
Sign up to set email alerts
|

Population metabolism of Nebria brevicollis (F.) (Coleoptera: Carabidae)

Abstract: The respiratory metabolism of all life stages of a predatory beetle was investigated. Measurements were made throughout the year in a continuously recording respirometer. The Warburg respirometer was used to examine the relationship between oxygen cosumption and temperature.Respiration was affected by several factors. No periodicity in respiration was observed during the 24 hour period. During the breeding season the males showed a significantly higher respiratory rate than the females. Temperature influence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The Qlo values calculated in this study were: N g a v i s 2.18 (males) and 1.72 (females); N.philippi 2.12 (males) and 2.15 (females). These are slightly lower values than those reported for other carabids: 2.90-3.37 for Nebria brevicollis (Manga, 1972) and 2.3-3.0 for Pterostichus coerulescerts L. (Mols, 1988); but are in close agreement with the Van?…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The Qlo values calculated in this study were: N g a v i s 2.18 (males) and 1.72 (females); N.philippi 2.12 (males) and 2.15 (females). These are slightly lower values than those reported for other carabids: 2.90-3.37 for Nebria brevicollis (Manga, 1972) and 2.3-3.0 for Pterostichus coerulescerts L. (Mols, 1988); but are in close agreement with the Van?…”
Section: Resultssupporting
confidence: 67%
“…Very little has been published on the respiratory metabolism of carabids. The studies on two European species, Pterostichus coerulescerzs (Mols, 1988) and Nebria brevicollis (Manga, 1972) provide recent information and summarize the relevant literature. Most researchers have found or assumed that there is no difference between the respiration rates of male and female carabids (Mols, 1988).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high net production efficiency (Pg/A = 60.3%, P 8 + PeviA = 66%) in C. cornutus may result from its ability to conserve energy by metabolic compensation to seasonal temperatures, which as discussed above, may be unique among insects. Production efficiency for other insects are 5-25% below that for hellgrammites (e.g., McDiffett 1970, Lawton 197Ia, Bailey and Riegert 1972, Heiman and Knight 1975, Randolph et al 1975 Total Pev by C. cornutus (13.4%) falls within the range (2.7-14.7%) reported for other insects (e.g., Dutton 1968, McDiffett 1970, Lawton 1971a, Manga 1972, Bailey and Riegert 1972, Randolph et al 1975).…”
Section: Individual Energy Budgetmentioning
confidence: 51%
“…Dispersal within the grid seemed to be random. Several authors (Nelson 1970, Manga 1972, Ericson 1977 have used marking methods (branding and scraping of the elytra) which are similar to the method employed in this study. They concluded that such marking had no effect on vitality or survival.…”
Section: Scarites Substriatusmentioning
confidence: 99%